Gentirigeoside B from Gentiana rigescens Franch Prolongs Yeast Lifespan via Inhibition of TORC1/Sch9/Rim15/Msn Signaling Pathway and Modification of Oxidative Stress and Autophagy - Lan Xiang; Dejene Disasa; Yanan Liu; Rui Fujii; Mengya Yang; Enchan Wu; Akira Matsuura; Jianhua Qi (MDPI AG, 2022)
Gentirigeoside B (GTS B) is a dammaren-type triterpenoid glycoside isolated from G. rigescens Franch, a traditional Chinese medicinal plant. In the present study, the evaluation of the anti-aging effect and action mechanism analysis for this compound were conducted. GTS B significantly extended the replicative lifespan and chronological lifespan of yeast at doses of 1, 3 and 10 μM. Furthermore, the inhibition of Sch9 and activity increase of Rim15, Msn2 proteins which located downstream of TORC1 signaling pathway were observed after treatment with GTS B. Additionally, autophagy of yeast was increased. In addition, GTS B significantly improved survival rate of yeast under oxidative stress conditions as well as reduced the levels of ROS and MDA. It also increased the gene expression and enzymatic activities of key anti-oxidative enzymes such as Sod1, Sod2, Cat and Gpx. However, this molecule failed to extend the lifespan of yeast mutants such as ∆cat, ∆gpx, ∆sod1, ∆sod2, ∆skn7 and ∆uth1. These results suggested that GTS B exerts an anti-aging effect via inhibition of the TORC1/Sch9/Rim15/Msn signaling pathway and enhancement of autophagy. Therefore, GTS B may be a promising candidate molecule to develop leading compounds for the treatment of aging and age-related disorders.